In vivo activation of peripheral blood polymorphonuclear neutrophils by gamma interferon results in enhanced fungal killing. - Morrison, C J (1989)
The effect of in vivo administration of murine recombinant gamma interferon (IFN) on the fungicidal activity of murine peripheral blood polymorphonuclear neutrophils (PB-PMNs) was studied. Mice were injected intramuscularly with 250, 2,500, 25,000 or 250,000 U of IFN 5 h before collection of peripheral blood. Purified PB-PMNs were cocultured in vitro with Blastomyces dermatitidis yeast cells for 2 h. PB-PMNs from untreated mice killed 44.5 +/- 12.5% of the fungal inoculum, whereas PB-PMNs from mice treated with 25,000 or 250,000 U of IFN showed significantly enhanced in vitro killing (68.0 +/- 9.4% [P less than 0.005] and 72.3 +/- 1.1% [P less than 0.001], respectively). Treatment with 250 or 2,500 U of IFN or 25,000 U of heated (100 degrees C, 15 min) IFN had no effect. The IFN-induced activation of PB-PMNs was transitory. Significant enhancement of PB-PMN killing activity occurred 1, 2, or 5 h after in vivo IFN administration, but no enhancement was observed 16 or 24 h after IFN treatment. Enhanced fungicidal activity by PB-PMNs from mice treated for 5 h with 25,000 U of IFN correlated with an increased release of superoxide anion (O2-) in vitro after stimulation of PB-PMNs with phorbol ester; normal PB-PMNs and IFN-activated PB-PMNs, respectively, produced 2.2 +/- 2.5 and 23.5 +/- 4.8 nmol of O2- per 10(6) PB-PMNs per 30 min (P less than 0.005). The exogenous addition of compounds that antagonize or inhibit the formation of oxygen radicals (superoxide dismutase, catalase, dimethyl sulfoxide, or sodium azide) significantly inhibited fungal killing by both normal and IFN-activated PB-PMNs. In addition to the enhanced microbicidal activity and superoxide generation demonstrated in vitro with constant cell numbers, there was a transient leukocytosis (particularly neutrophilia) in peripheral blood at doses of IFN and at times after IFN administration where enhanced activity was also demonstrated. In summary, our results indicate that PB-PMNs can be activated in vivo for enhanced killing of a fungal target. The enhanced killing capacity of IFN-activated PB-PMNs is due at least in part to the enhancement of oxidative killing mechanisms.